Behaviour change practices in exercise referral schemes: developing realist programme theory of implementation - John Downey; Katie Shearn; Nicola Brown; Ross Wadey; Jeff Breckon (BMC, 2021)
Abstract Background Exercise Referral Schemes have been delivered worldwide in developed countries to augment physical activity levels in sedentary patients with a range of health issues, despite their utility being questioned. Understanding the implementation mechanisms of behaviour change practices is important to avoid inappropriate decommissioning and support future service planning. The aim of this study was to develop initial theories to understand what influences the behaviour change practices of Exercise Referral practitioners within the United Kingdom. Methods An eight-month focused ethnography was undertaken, to carry out the first phase of a realist evaluation, which included participant observation, interviews, document analysis, and reflexive journaling. A comprehensive implementation framework (Consolidated Framework for Implementation Research) was adopted providing an extensive menu of determinants. Mechanisms were categorised based on the Theoretical Domains Framework (within the Capability, Opportunity, Motivation, Behaviour model) providing an explanatory tool linking the levels of the framework. Results Three programme theories are proposed. Firstly, motivation and capability are influenced when behaviour change oriented planning and training are in place. Secondly, motivation is influenced if leadership is supportive of behaviour change practice. Lastly, integration between health professionals and practitioners will influence motivation and capability. The conditions necessary to influence motivation and capability include a person-centred climate, cognizant practitioners, and established communities of practice. Conclusions The findings are the first to articulate the necessary elements for the implementation of behaviour change practices in Exercise Referral services. These results outline emerging theories about the conditions, resources, and explanations of behaviour change implementation that can inform service development.